2020
DOI: 10.1200/po.19.00248
|View full text |Cite
|
Sign up to set email alerts
|

Unique Genomic Landscape of High-Grade Neuroendocrine Cervical Carcinoma: Implications for Rethinking Current Treatment Paradigms

Abstract: PURPOSE High-grade neuroendocrine cervical cancer (HGNECC) is an uncommon malignancy with limited therapeutic options; treatment is patterned after the histologically similar small-cell lung cancer (SCLC). To better understand HGNECC biology, we report its genomic landscape. PATIENTS AND METHODS Ninety-seven patients with HGNECC underwent comprehensive genomic profiling (182-315 genes). These results were subsequently compared with a cohort of 1,800 SCLCs. RESULTS The median age of patients with HGNECC was 40.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 29 publications
3
32
3
Order By: Relevance
“…However, our data show that this is not the case. In SCLC, TP53 mutations are reported in 86–93% and RB1 mutations in 40–62% ( Peifer et al 2012 , Dowlati et al 2016 , Miyoshi et al 2017 , Eskander et al 2020 ) while biallelic inactivation of TP53 and RB1 (by any mechanism) is a universal finding for all SCLC ( George et al 2015 ). The 2019 WHO classification for digestive tumours state that GEP-NEC frequently have TP53 and RB1 mutations ( WHO 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our data show that this is not the case. In SCLC, TP53 mutations are reported in 86–93% and RB1 mutations in 40–62% ( Peifer et al 2012 , Dowlati et al 2016 , Miyoshi et al 2017 , Eskander et al 2020 ) while biallelic inactivation of TP53 and RB1 (by any mechanism) is a universal finding for all SCLC ( George et al 2015 ). The 2019 WHO classification for digestive tumours state that GEP-NEC frequently have TP53 and RB1 mutations ( WHO 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the very limited results of first and second line chemotherapy for GEP-NEC ( Sorbye et al 2013 , 2019 , Garcia-Carbonero et al 2016 ), the possibility to apply targeted therapy in GEP-NEC thus seems to be a major possibility to improve the very poor prognosis of these patients. Extrapolation from SCLC has also been a common practice for the treatment of all extrapulmonary neuroendocrine carcinomas, but a recent report shows major genetic differences between SCLC and neuroendocrine cervical carcinoma (HGNECC), further questioning such a general extrapolation ( Eskander et al 2020 ). The HGNECC genetics are also different compared to our GEP-NEC findings, illustrating that extrapulmonary NEC should not be assessed as a joint group but rather according to primary tumour site.…”
Section: Discussionmentioning
confidence: 99%
“…Although loss of RB1 is not registered in OncoKB, two recent studies described that the deregulation of cell cycle transitions upon loss of RB1 can represent a high dependency on aurora kinases, which can be targeted therapeutically [ 31 , 32 ]. Recently, Ramez et al reported that 73% of patients with NECC had potentially actionable genetic alterations by analyzing 97 cases of NECC using comprehensive genomic profiling (182–315 genes) [ 11 ]. Despite extensive research, some genetic alterations, including RET mutations, were first identified in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, genomic data available for NECC are still very limited, particularly for Asian patients, although some previous studies reported recurrent genetic alterations involving the phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT)/mechanistic target of rapamycin (mTOR), mitogen-activated protein kinase (MAPK), and P53 pathways in NECC [ 9 , 10 , 11 , 12 ]. One of these reports on comparison of genomic profiles between NECC and SCLC demonstrated considerably different molecular characteristics [ 11 ], whereas another report revealed genetic similarities between NECC and other major cervical cancer subtypes, including SCC and adenocarcinoma (ADC), using published genomic data [ 12 ]. Considering the genomic differences between NECC and SCLC, the present treatment strategy for NECC complying with that for SCLC could be optimized based on the specific genetic features of NECC.…”
Section: Introductionmentioning
confidence: 99%
“…5 As outlined in the report by Arakawa et al, the first patient was found to have a neuroendocrine cervical carcinoma, which is notoriously difficult to treat, although recent reports suggest benefit with immune checkpoint inhibition in particular patients with high-grade disease. 6,7 Patient 1 was described as having a mixed response following cytotoxic chemotherapy and was ultimately treated with single-agent nivolumab on clinical trial with a complete response. It is unclear if this malignancy exhibited mismatch repair deficiency or was microsatellite unstable-high (MSI-high), both predictors of response to immune checkpoint inhibition.…”
mentioning
confidence: 99%